Removing fluoride from hot spring wastewater by an electrolysis system with a perforated plate as a diaphragm - Yuki Imai; Tomonori Kawakami (Cogent Engineering, 2020)
A continuous electrolysis system using an electrolysis reactor cell separated into an anode cell and a cathode cell by a perforated plate as a diaphragm was operated in a laboratory to remove fluoride (F-) from hot spring wastewater to meet the Japanese national minimum effluent standard for F- of 8 mg/L. The perforated plate was 5 mm thick and had 740 holes with a diameter of 1.2 mmφ. F- was removed by co-precipitation with magnesium hydroxide (Mg(OH)2) produced in the cathode cell. Water from Gero Hot Spring containing 17.0 mg/L of F- was used as a model wastewater. Since Gero Hot Spring water does not contain magnesium (Mg2+), magnesium carbonate (MgCO3) was added as a form of slurry into the anode cell with the hot spring water. The hot spring water containing Mg2+ passed through the perforated plate and flowed into the cathode cell, where Mg(OH)2 was co-precipitated with F- due to hydroxide ion (OH-) produced by electrolysis. Alkalinity (Alk), which interferes with the precipitation of Mg(OH)2 by forming MgCO3 in the cathode cell, was removed in the anode cell by hydrogen ion (H+) produced by electrolysis. Various combinations of the added Mg2+ concentration (Mgi) and the applied current (Ia) were tested to elucidate the effect of these parameters on F- removal (ΔF). It was revealed that, less than 8 mg/L of the F- concentration in treated water (F (treated)), which is the Japanese national minimum standard for wastewater, was achieved when the Mgi was between 85 and 110 mg/L and Ia was more than 90 mA.